Danone Netherlands Learning and Development Strategy to Improve Emotional Intelligence in Team Leaders - Agustinus Kadek Kevin Christian (iBuss Management, 2022)
Team leaders play an essential role in the success of a team and the organization as they occupy the position of responsibility. It is essential to find the right factors that make an effective team leader improve their effectiveness. External literature has found a positive correlation between leadership and emotional intelligence compared to managerial skills. Team leaders who use emotional intelligence can leverage their technical capabilities to bring the best out of their peers and achieve high performance. Emotional intelligence has 12 competencies that could be developed and trained to create highly effective team leaders. After a thorough assessment, it has been found that Danone Netherlands’ team leaders lack adaptability, conflict management, organizational awareness, self-regulation, and coaching. The Learning and Development team has its set of training programs. After an assessment to align it with emotional intelligence competencies, it has been found that the competencies of adaptability and conflict management lack training programs. It is recommended that Danone Netherlands’ learning team implement the recommended modules to fulfill the gap in adaptability and conflict management skills.Keywords: Team leaders, Emotional intelligence, Learning and development